Development and characterization of an automated imaging workflow to generate clonally‐derived cell lines for therapeutic proteins. (10th October 2017) - Shaw, David; Yim, Mandy; Tsukuda, Joni; Joly, John C.; Lin, Andy; Snedecor, Brad; Laird, Michael W.; Lang, Steven E.
Abstract : In the development of biopharmaceutical products, the expectation of regulatory agencies is that the recombinant proteins are produced from a cell line derived from a single progenitor cell. A single limiting dilution step followed by direct imaging, as supplemental information, provides direct evidence that a cell line originated from a single progenitor cell. To obtain this evidence, a high‐throughput automated imaging system was developed and characterized to consistently ensure that cell lines used for therapeutic protein production are clonally‐derived. Fluorescent cell mixing studies determined that the automated imaging workflow and analysis provide ∼95% confidence in accurately and precisely identifying one cell in a well. Manual inspection of the images increases the confidence that the cell line was derived from a single‐cell to >99.9%. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 34:584–592, 2018